2021
DOI: 10.1177/00111287211007742
|View full text |Cite
|
Sign up to set email alerts
|

Providing Support to Victims: Police Officers’ Service Referral Provision and Advocate Involvement in Domestic Violence Incidents

Abstract: Limited research has investigated police service provision and advocate involvement in domestic violence (DV) incidents. This study used a stratified random sample of 368 cases from an urban police department to assess police officers’ decisions to provide service provision and to involve an advocate in formally-reported DV incidents. Multivariate binary logistic regression models revealed decreased suspect age and presence of physical abuse significantly increased service referral. Advocate involvement signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Third, supporting Hypothesis 1c, our results showed that perceived severity of IPVAW was related to proactive attitudes towards intervention in IPVAW cases, which is in accord with prior research (Goodson et al, 2022;Gracia et al, 2008;Kebbell, 2022). Importantly, the tested mediation model confirmed that the perceived severity of IPVAW is the explanatory mechanism that underlies the negative relationship between IPVAW myths and proactive attitudes toward intervention in gender violence, confirming our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Third, supporting Hypothesis 1c, our results showed that perceived severity of IPVAW was related to proactive attitudes towards intervention in IPVAW cases, which is in accord with prior research (Goodson et al, 2022;Gracia et al, 2008;Kebbell, 2022). Importantly, the tested mediation model confirmed that the perceived severity of IPVAW is the explanatory mechanism that underlies the negative relationship between IPVAW myths and proactive attitudes toward intervention in gender violence, confirming our Hypothesis 2.…”
Section: Discussionsupporting
confidence: 90%
“…Drawing from Banyard's bystander intervention model ( 2011), studies also have indicated that the perceived severity of IPVAW is an influencing factor in the decision-making process involved in providing help in gender-based violence episodes (Banyard, 2011;Gracia et al, 2008Gracia et al, , 2009. A cross-cultural body of research has indicated that perception of severity, urgency, or high risk in IPVAW cases promoted the allocation of additional resources in Australia (Kebbell, 2022), lesser legitimization, and higher credibility and service referral in the U.S. (Goodson et al, 2022), as well as preferences for actions regardless of the victim's wishes and stronger feelings of responsibility in Spain (Gracia et al, 2008). However, even though police officers tend to recognize and prefer greater involvement, nuances have been found concerning how they evaluate the severity of different IPVAW incidents (Gracia et al, 2008;Robinson et al, 2016).…”
Section: Ipvaw Myths and Police Officers' Perceived Severity Of Ipvawmentioning
confidence: 99%
See 1 more Smart Citation
“…While provision of victim supports was low (i.e., 10% of cases), Swerin et al (2018) also found that children’s presence during IPV-arrest incidents increased the odds of police providing supports/referrals to the victim. In contrast, Goodson et al (2022) found just over 70% of victims were provided with service referrals by police, although children’s presence had no impact on service referral provision. Hatten and Moore (2010) recommended a pamphlet with victim services information be created to ensure supports are offered to every victim after they found that police were less likely to contact victim services depending on situational characteristics (e.g., victim substance use, male victim).…”
Section: Introductionmentioning
confidence: 85%
“…It is also noteworthy that embedded advocates were involved in only about half of the cases in this sample. The importance of service referral and advocate involvement cannot be understated as this has the potential to mitigate trauma, facilitate victim cooperation, and enhance IPV case processing (Goodson et al, 2020(Goodson et al, , 2021Camacho & Alarid, 2008). Resource provision may be particularly important for Latina immigrant IPV victims because they have encountered increased barriers and significant impediments from social and justice entities (Ammar et al, 2005;Menjívar & Salcido, 2002;Raj & Silverman, 2002;Sokoloff & Dupont, 2005).…”
Section: Discussionmentioning
confidence: 99%